The L-shaped relationship between composite dietary antioxidant index and sarcopenic obesity in elderly adults: a cross-sectional study - Wu, He; Chen, Xiyi; Shi, Zhengqing; Liu, Jieyu; Meng, Ziqi; Zheng, Chenguo; Zhou, Chongjun (Frontiers in Nutrition, 2024)
Background This study aimed to examine the associations of the Composite Dietary Antioxidant Index (CDAI) with sarcopenic obesity (SO) using the National Health and Nutrition Examination Survey (NHANES) database. Methods Data were gathered from NHANES between 2001 and 2004. To examine the relationship between CDAI and the occurrence of SO, multiple logistic regression analyses were performed. Subgroup analyses were performed to demonstrate the stability of the results. Restricted cubic splines were utilized to examine the non-linear correlations. Results A total of 2,333 elderly individuals were included in the study. In the multivariate logistic regression crude model, we revealed an odds ratio (OR) of 0.928 [95% confidence interval (CI), 0.891–0.965, p < 0.001] for the correlation between CDAI and SO. The ORs were 0.626 (95% CI, 0.463–0.842) and 0.487 (95% CI, 0.354–0.667) for CDAI tertiles 2 and 3, respectively (p for trend <0.001), after full adjustment. The subgroup analysis findings demonstrated a reliable and enduring connection between CDAI and SO across various subgroups. However, the strength of the correlation between CDAI and SO was significantly affected by diabetes (p for interaction = 0.027). Moreover, restricted cubic spline analysis revealed an L-shaped relationship. Conclusion The present study identified an L-shaped correlation between CDAI and SO in elderly participants’ demographics. The implications of these findings were significant for future studies and the formulation of dietary guidelines.